2016
DOI: 10.1109/tbme.2015.2480242
|View full text |Cite
|
Sign up to set email alerts
|

A Method for Automatic and Objective Scoring of Bradykinesia Using Orientation Sensors and Classification Algorithms

Abstract: Correct assessment of bradykinesia is a key element in the diagnosis and monitoring of Parkinson's disease. Its evaluation is based on a careful assessment of symptoms and it is quantified using rating scales, where the Movement Disorders Society-Sponsored Revision of the Unified Parkinson's Disease Rating Scale (MDS-UPDRS) is the gold standard. Regardless of their importance, the bradykinesia-related items show low agreement between different evaluators. In this study, we design an applicable tool that provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 27 publications
0
42
1
3
Order By: Relevance
“…In addition to analyzing the diversities of tapping patterns performed by the patients with motor impairments, our goal was to offer a minimal set of sensors and maximal information for clinicians. Several authors performed tapping assessment with only one sensor placed on the index finger and calculated the angle of the finger relative to the vertical axis [8,17,37,38] or, having the hand placed on a table, defined the zero-angle when the finger is down [39]. Although the majority of movement in finger tapping is performed by the index finger, we have found that it was important to also have a sensor on the thumb.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition to analyzing the diversities of tapping patterns performed by the patients with motor impairments, our goal was to offer a minimal set of sensors and maximal information for clinicians. Several authors performed tapping assessment with only one sensor placed on the index finger and calculated the angle of the finger relative to the vertical axis [8,17,37,38] or, having the hand placed on a table, defined the zero-angle when the finger is down [39]. Although the majority of movement in finger tapping is performed by the index finger, we have found that it was important to also have a sensor on the thumb.…”
Section: Discussionmentioning
confidence: 99%
“…The tapping test has been widely used for assessment of ataxia [2], stroke recovery [3], Alzheimer’s disease [4], and of bradykinesia in Parkinson’s disease (PD) [5,6,7,8,9]. It is included in the Unified Parkinson’s disease rating scale (MDS-UPDRS test, [10]).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations